Debating as a Tool Promoting Thinking Process - Ročāne, Maija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The teaching method – debating is a way how to encourage students to participate actively in their own learning process. The teaching method-debating is offered in the curricula of the foreign language subject in lower secondary and general secondary education in Latvia besides the other teaching methods, e.g. discussion, questions, role play, conversation, narration, etc. Through applying this teaching method the teacher is no longer the only source of information. This article is focusing on the promotion of the thinking process through debating, as well as the opportunities of bringing the teaching methoddebating to the lesson. It is important to encourage students to think. Unfortunately, often the focus of the lesson is put on the tasks that rather contribute to discipline than thinking.